2013
DOI: 10.1002/jps.23546
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Oxytocin Dimers is Suppressed by the Zinc-Aspartate-Oxytocin Complex

Abstract: ABSTRACT:The aim of this study was to investigate the effect of divalent metal ions (Ca, Mg 2+ , and Zn 2+ ) on the stability of oxytocin in aspartate buffer (pH 4.5) and to determine their interaction with the peptide in aqueous solution. Reversed-phase high-performance liquid chromatography and high-performance size-exclusion chromatography measurements indicated that after 4 weeks of storage at 55 • C, all tested divalent metal ions improved the stability of oxytocin in aspartate-buffered solutions (pH 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…Initially, samples contained 50 mM ZnCl 2 (10 mM aspartate buffer, pH 4.5) to stabilize OT via chelation 16 prior to subsequent sample preparation (e.g. removing proteins via protein precipitation (PPT)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, samples contained 50 mM ZnCl 2 (10 mM aspartate buffer, pH 4.5) to stabilize OT via chelation 16 prior to subsequent sample preparation (e.g. removing proteins via protein precipitation (PPT)).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that strong protein binding was preventing detection of endogenous OT ((<pg/mL levels, Figure SM 4 ) due to co-precipitation during PPT. The disulfide bridge (DSB) of OT ( Figure 2a ) can engage in complexes 16 , and likely with serum albumin (buminlbumi, which contains multiple DSBs. To obstruct plasma protein binding, a reduction/alkylation (R/A) 14 step was performed which irreversibly breaks DSBs ( Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…292 The extent of the formation of reactive oxygen species in the presence of human and rat amylin and Cu(II) was investigated in another study. 296,297 The effect of Ca(II), Mg(II) and Zn(II) was investigated and the latter metal ion was found to be the most efficient. 293 The metal complexes of human IAPP and its fragments have been investigated by ESI-MS technique and the residues between position 22-26 were identified as the primary Cu(II) binding sites.…”
Section: Metal Complexes Of Peptide Fragments Of Prion Proteinmentioning
confidence: 99%
“…Multiple degradation pathways lead to OT instability (6,7,16). Degradation is mainly the result of chemical instability at the disulfide bond leading to dimerization and formation of sulfur-related impurities such as trisulfide, tetrasulfide, and trimers (16)(17)(18). Instability at the glutamine and asparagine groups leads to deamidation products.…”
Section: Introductionmentioning
confidence: 99%
“…Instability at the glutamine and asparagine groups leads to deamidation products. OT stability in solution can be improved by using stabilizing agents, in particular buffers and divalent cations (7,17,18). Recently, Avanti et al demonstrated the beneficial effect of combining divalent zinc and a citrate buffer that dramatically reduced the formation of dimers and other sulfur-related impurities in solution (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%